The lithologic differences between the third and fourth members of the Eocene Shahejie Formation in the Bohai Bay Basin and the associated climatic evolution. (19th June 2017) - Wu, Liangjun; Wang, Fukui; Wang, Dehai; Fu, Mao; Jia, Yuhua
Abstract : The Bohai Bay Basin straddled the Eocene boundary between arid and wet climates in eastern China. The basin was simultaneously affected by both arid and wet climates, and contemporaneous sediments developed under both extremely arid and extremely wet conditions. Data from every well drilled in the oil fields in the Bohai Bay Basin have been used to study the lower fourth member and the upper third member of the Shahejie Formation. The spatial distribution of climate indicators in the lower fourth member of the Shahejie Formation shows that the climate boundary extended from the northern Jizhong Depression to the Bozhong Depression. The portion of the basin to the north of this boundary mostly developed coalbeds, dark mudstone, and oil shale (indicative of a warm and wet climate), whereas the portion of the basin to the south of this boundary mostly developed gypsum, rock salt, and magenta dolomitic mudstone (indicative of a hot and arid climate). During the formation of the upper third member of the Shahejie Formation, the climate boundary shifted southward to the region between the southern part of the Jizhong Depression and the Jiyang Depression. The wet climate zone in the north expanded southward, and the arid climate zone in the south shrank. This shift is evident in the vertical lithologic characteristics of the members that formed before and after this shift in the climate boundary. The lithologic succession in the central part of the basin exhibits significant changes, whereas the lithologic successions in the southern and northern parts of the basin remain homogeneous and stable through time. Therefore, between the formation of the third and fourth members of the Eocene Shahejie Formation, the Bohai Bay Basin experienced a significant climate change. This change directly affected the pattern of the Eocene climate zones in eastern China and is indicative of changes in the paleoclimate zones near the Tropic of Cancer.